Comparison in physical geography lessons - Jakoveris, M.; Stankūnienė, E. (Psichologija, 1962)
Comparison plays an important role in the cognitive processes of objective laws of natural and social development. Marxism-Leninism classics made a wide use of it by analyzing the regularities of society development. Comparison in geography science is also widely applied for establishment of the laws of natural progress.Reorganizing schools and seeking to actively assist students in learning to assimilate the taught material and consolidate their knowledge, a significant role is played by comparisons which foster students’ thinking and allow them avoiding formalism in learning.Despite that, the matter of using comparison in learning processes is scarcely investigated.In this article the authors examine some instances of comparison used in teaching the school course on Physical Geography. According to the authors, the concepts of contrasting and comparison should be separated. Contrasting is understood by the authors as simple juxtaposition of territories and other geographical objects to each other without any deeper analysis. Comparison, on the other hand, is defined as juxtaposition which is followed by a deep analysis of phenomena and objects. This analysis can be performed according to the following plan: a) explication of similarities, b) explication of differences, c) explication of the reasons conditioning these similarities and differences.The authors subdivide contrasting and comparison into the ordinary and complex. The first include: numerical, visual, and literary contrasting; the second-componential and complex comparison.The numerical contrasting shows the ratio of territories and objects expressed in numbers.The visual contrasts show in brief visual form the essence of the investigated objects.The literary contrasts in brief literary form reveal the characteristic traits of geographical objects.The componential comparison is a comparison conducted according to the components of natural environment (relief, climate, soil, and vegetation).The complex comparison is carried out with regard to all the complex of physical-geographical conditions of the compared territories.The article reviews the methods of usage of comparisons in Geography lessons in teacher’s speech, application of visual aids and performing practical works. Moreover, comparisons are analyzed in their application during different structural parts of a lesson: revising and questioning, lecturing the new material, assigning homework.At the end of the article, short generalizations and conclusions are provided.1. The use of comparison allows:a) Better explanation of natural phenomena previously unknown to students; b) developing students’ geographical thinking; c) integrating separate units of the school Geography course; d) boosting teachers and students’ creative initiatives.2. Comparisons are used with the aim to:a) Formulate geographical concepts to students; b) highlight geographical relations and regularities; c) explicate the development processes of natural environment and societies; d) summarize and systemize the learned material; e) improve communist education of the youth.3. The use of the comparison method in lessons develops materialist outlook and dialectic thinking in students. Comparison activates the learning process and facilitates better assimilation of the syllabus; therefore, it should be widely used in school Geography lessons.
Keywords: geography; comparison; contrast